A Constraint-Driven Assessment of Operating Systems for Wearable Devices - Amorim, Vicente Jose Peixoto; Delabrida, Saul; Oliveira, Ricardo Augusto Rabelo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
Wearable devices have increasingly become popular in recent years. Devices attached to users body now remotely monitor his daily activities/health. However, some operating systems running on these devices were not initially designed and developed for this purpose, letting them have a poor performance or even requiring to spend more resources or better hardware. This work presents a comparison, driven by specific constraints, between operating systems for wearable devices. Our research raised the key constraints of this context and figured out which operating system has the best performance. Results presented here shows that evaluated operating systems do not have enough performance when considering wearable devices specific constraints, letting us conclude that improvements should be made.